MIG PV Process: effect of negative electrode proportion on aluminum weld bead geometry - Ruben Gonzalez, Leandro; Ruben Gonzalez, Arnaldo (Seven Editora, 2023)
The MIG (Metal Inert Gas) process with variable polarity is a relatively new process that can be applied in the welding process industry with high rates of productivity and competitive cost. The process uses compound curves of pulses in positive and negative polarities, and presents as main benefits in relation to the conventional process, high melting rate, allied to low heat input, smallerdeformations and better control of penetration and dilution. The objective of this work is to analyzethe effects of the proportions of the negative polarity (%EN), of the typical current curve of the process, seeking to relate with the penetration and dilution of the resulting weld bead. Three levelsof %EN percentages of 0%, 30% and 50% were used for the study. Weld beads were made in the flat position (1G), depositing ER5356 aluminum onto the free surface of Al5052-F sheet. The negative polarity parameters used were compared with different forms of calculations proposed inthe literature for determining the value of the negative electrode ratio. It is suggested that for the calculation of the negative electrode ratio (% EN), all parameters of the curve (currents and times)should be considered in order to obtain an effective comparison of the % EN levels. It was concluded that increasing the proportion of negative electrode causes decreased penetration and dilution in the weld bead. DOI: 10.56238/pacfdnsv1-044